Increased user engagement on YouTube for loot box content and its potential relevance for behavioural addictions - Elke Smith; Yannik Poth; Kara S. Z. Sohns; Kai Kaspar; Jan Peters (Scientific Reports)
Abstract Video games frequently contain loot boxes, i.e. virtual in-game items sharing structural similarities with gambling. On YouTube©, there are multi-million subscriber channels prominently featuring loot box-related content. A gamblification of digital games may increase player engagement, and we tested if user engagement on YouTube is linked to loot box content. We extracted aggregate user engagement measures from more than 22 thousand YouTube gaming videos with and without focused display of loot boxes. Principal component analysis was used to reduce dimensionality and derive components reflecting overall and sustained, and relative user engagement, respectively. Confirming our pre-registered hypothesis (see https://osf.io/nh7zr ), a significant effect of loot box content on the first principal component was found, reflecting higher overall and sustained user engagement for videos featuring loot box content. This increased engagement may be linked to the gambling-like properties of the reward structure conveyed by loot boxes. Publicly available user data may serve as an early indicator of potential changes in problematic internet use and gambling-related behaviour.